2019
DOI: 10.7567/1347-4065/ab2c45
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lithium cobalt oxide films deposited by radio frequency magnetron sputtering as thin-film battery cathodes

Abstract: Herein, we describe the fabrication of LiCoO2 thin films by high-frequency (27.12 MHz) magnetron sputtering and investigate the effects of sputtering power and Ar/O2 ratio on their morphological and electrochemical properties. Films produced at higher sputtering powers and O2 proportions are shown to exhibit increased porosity and a greater number of surface active sites. The discharge capacity of the film prepared at a sputtering power of 180 W and an Ar/O2 ratio of 1/2 is determined as 22.894 μAh μm–1 cm–2 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…The corresponding Coulomb efficiency is ≈93% for every charge/discharge cycle. The obtained discharge capacities of the first cycle are higher than for a sputter power optimized LCO thin film like it is shown in Jan et al [ 28 ] Altough the discharge capacities in Zhu et al are quite higher than for the thin films presented in this work, the Coulombic efficiency of 93% is higher in this case. [ 29 ] However, the capacity fading in the publication of Zhu et al is even bigger (≈3.7%) [ 29 ] than for the films reported in here (≈0.7%).…”
Section: Resultssupporting
confidence: 60%
“…The corresponding Coulomb efficiency is ≈93% for every charge/discharge cycle. The obtained discharge capacities of the first cycle are higher than for a sputter power optimized LCO thin film like it is shown in Jan et al [ 28 ] Altough the discharge capacities in Zhu et al are quite higher than for the thin films presented in this work, the Coulombic efficiency of 93% is higher in this case. [ 29 ] However, the capacity fading in the publication of Zhu et al is even bigger (≈3.7%) [ 29 ] than for the films reported in here (≈0.7%).…”
Section: Resultssupporting
confidence: 60%
“…Since lithium ion motion occurs within the (003) planes in LCO, it is desirable for these planes to intersect the cathode surface, minimizing the impedance of the cathode-electrolyte interface [10,12]. Previous reports have shown that this condition is most readily satisfied by the parallel alignment of (104) and (101) planes with the film surface [2,10,[13][14][15][16][17]. Numerous investigations have studied the effects of altering the main RF sputter deposition and post-deposition processing conditions (RF power density, process pressure, process gas composition, substrate material, substrate temperature during deposition and post-deposition annealing temperature) on the properties of LCO thin films [2,7,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Usually, the deposition rate achieved by RF sputtering is directly proportional to the power density applied to the target [39]. Furthermore, a high power density may lead to favourable film properties, since several reports have shown that increasing the power density increases the crystallinity of asdeposited LCO films and reduces the formation of the electrochemically inactive cubic (𝐹𝑑3 ̅ 𝑚) Co3O4 phase [17,28,29]. The deposition rate is also sensitive to the process gas pressure; an increase in the pressure reduces the mean free path of sputtered atoms so that a smaller proportion reach the substrate, while a decrease in pressure reduces the frequency of collisions between the gas ions and the target, thereby lowering the sputtering rate [40].…”
Section: Introductionmentioning
confidence: 99%
“…Jan et al investigated LiCoO 2 films by variations in RF powers (120, 150, and 180 W) and gas ratios (Ar:O 2 , 1:2, 1:1, and 2:1) and found sputtering optimum conditions with an RF power of 180 W and (Ar:O 2 ,1:2). A columnar structure with a porous surface morphology was achieved by annealing in air at 700 • C for 1 h at a heating rate of 30 • C min -1 [19]. Trusk et al found the dependence of the formation of the (003) plane from the film thickness and sputtering gas: a gradual increase in thickness above 5 µm and sputtering in a mixture of Ar and O 2 were found to have an essential effect on the increment in the (003) plane, which is undesirable due to a hindered ionic diffusion [20].…”
Section: Introductionmentioning
confidence: 99%